Dampak Fasilitas dan Pelayanan Pramuwisata Terhadap Kepuasan Wisatawan di Destinasi Kota Tua - Amrullah, Amrullah; Taviprawati, Ervina; Prabandari, Wijayanti Dewi; Safirah, Jihaan (Jurnal Ilmiah Pariwisata, 2024)
This research aims to determine the effect of tourist facilities and services on tourist satisfaction. This research uses quantitative descriptive methods with multiple regression analysis. The location of this study is in Destanisi Old Town. The sample selection technique applied was Accidental Sampling. Research findings show that tourist facilities have a positive influence on tourist satisfaction, while tour guide services do not have a significant impact. Facilities and services in Kota Tua have an important role in increasing visitor satisfaction. Comprehensive facilities, good accessibility and friendly service can increase tourist comfort. However, tour guide services that only focus on museums can reduce satisfaction due to the lack of tour guides to accommodate visitors' needs. To improve the quality of tour guide services, the government is expected to provide training and educational programs. A skilled, friendly and responsive tour guide can significantly improve the tourist experience. Keywords: tourist facilities, tour guide services, tourist satisfaction